2019
DOI: 10.20473/ijar.v1i12019.19-25
|View full text |Cite
|
Sign up to set email alerts
|

Pain Level of Postoperative Orthopedic Patients at Dr. Soetomo General Hospital

Abstract: Introduction: Postoperative pain is the most undesirable consequence of the surgery. If it is not managed properly, it can lead to a long healing. However, assessment and treatment of postoperative pain in surgical wards still have not received attention. Differences in patient's pain level after surgery and after being transferred to the surgical ward is very important in monitoring the effectiveness postoperative pain management. Objective: This study was conducted to determine the overview of pain level exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Salah satunya ialah penelitian di Rumah Sakit Dr. Soetomo pada Januari 2009 hingga Desember 2010 yang mendapatkan bahwa 50,4% kasus infeksi didapatkan pada fraktur terbuka grade 3. 8 Infeksi terkait fraktur disebabkan oleh berbagai jenis bakteri dan fungi. Beberapa jenis bakteri yang dikaitkan dengan infeksi terkait fraktur meliputi Staphylococcus aureus, Streptococcus epidermidis, Escherichia coli, Enterobacter spp, Enterococci spp, Klebsiella spp, Proteus spp, Corynebacterium, Propionibacterium, Pseudomonas aeruginosa, Acinetobacter baumannii, Clostridium spp, dan Aeromonas spp.…”
Section: Pendahuluanunclassified
“…Salah satunya ialah penelitian di Rumah Sakit Dr. Soetomo pada Januari 2009 hingga Desember 2010 yang mendapatkan bahwa 50,4% kasus infeksi didapatkan pada fraktur terbuka grade 3. 8 Infeksi terkait fraktur disebabkan oleh berbagai jenis bakteri dan fungi. Beberapa jenis bakteri yang dikaitkan dengan infeksi terkait fraktur meliputi Staphylococcus aureus, Streptococcus epidermidis, Escherichia coli, Enterobacter spp, Enterococci spp, Klebsiella spp, Proteus spp, Corynebacterium, Propionibacterium, Pseudomonas aeruginosa, Acinetobacter baumannii, Clostridium spp, dan Aeromonas spp.…”
Section: Pendahuluanunclassified
“…Responsive analgesia management with good communication can help lower postoperative pain incidence. 7 There is not much data regarding postoperative pain incidence in Indonesia. A study in Soetomo General Hospital at Surabaya had shown 30% of patients had developed postoperative pain after surgery.…”
mentioning
confidence: 99%